1995
DOI: 10.1021/tx00050a001
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Modification of Rat Liver Dipeptidyl Peptidase IV (CD26) by the Nonsteroidal Anti-Inflammatory Drug Diclofenac

Abstract: Diclofenac is a nonsteroidal anti-inflammatory drug that has been implicated in several cases of severe hepatotoxicity. Our previous study showed that diclofenac metabolites bound covalently and selectively to rat liver plasma membrane proteins with estimated monomeric masses of 110, 140, and 200 kDa. We report here that we have identified the 110 kDa diclofenac-labeled protein in rat liver as dipeptidyl peptidase IV, also known as CD26. In addition, we found that the activity of dipeptidyl peptidase IV in liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 22 publications
(27 reference statements)
0
42
0
1
Order By: Relevance
“…Boelsterli (2003) also described the occurrence of DCF acyl-glucuronids in humans and experimental animals, which remain reactive and can lead to protein adducts unless scavenged by glutathion. In trout, DCF is possibly also partially excreted as reactive DCF acyl-glucuronide via the kidney, where it could provide for protein adducts, as has been described previously in the liver where these adducts are considered causal in the observed idiosyncratic hepatotoxicity (Kretz-Rommel and Boelsterli, 1994;Hargus et al, 1994Hargus et al, , 1995. The formation of DCF-protein adducts may also be responsible for kidney pathology described for DCF exposed humans and fish (Hickey et al, 2001;Oaks et al, 2004;Risebrough, 2004;Schwaiger et al, 2004).…”
Section: Discussionmentioning
confidence: 66%
“…Boelsterli (2003) also described the occurrence of DCF acyl-glucuronids in humans and experimental animals, which remain reactive and can lead to protein adducts unless scavenged by glutathion. In trout, DCF is possibly also partially excreted as reactive DCF acyl-glucuronide via the kidney, where it could provide for protein adducts, as has been described previously in the liver where these adducts are considered causal in the observed idiosyncratic hepatotoxicity (Kretz-Rommel and Boelsterli, 1994;Hargus et al, 1994Hargus et al, , 1995. The formation of DCF-protein adducts may also be responsible for kidney pathology described for DCF exposed humans and fish (Hickey et al, 2001;Oaks et al, 2004;Risebrough, 2004;Schwaiger et al, 2004).…”
Section: Discussionmentioning
confidence: 66%
“…Although diclofenac was shown to bind irreversibly to hepatic microsomal proteins in several studies (Kretz‐Rommel and Boelsterli 1994; Hargus et al. 1995; Obach et al. 2008), the targeted polypeptides are still unidentified.…”
Section: Introductionmentioning
confidence: 99%
“…DCF-AG undergoes these rearrangements as the pH changes from acidic to physiologic conditions such as those that occur in the GI tract (Ebner et al, 1999;Kenny et al, 2004). DCF-AG can form adducts with multiple proteins in the liver and GI tract, and dipeptidyl peptidase IV was identified as a DCF-AG target in rat liver, where adduction resulted in decreased activity (Hargus et al, 1995). Furthermore, it was found that broadacting UGT inhibitors can significantly diminish the covalent binding of DCF metabolite to hepatocellular proteins in vitro (Kretz-Rommel and Boelsterli, 1993).…”
Section: Introductionmentioning
confidence: 99%